the Generative Engine Optimization (GEO) Strategy In Maintaining Corporate Reputation Authenticity In The Artificial Intelligence Era: A Conceptual Study On Goto Group - Septian Adhi Nugroho Septian; Bagas Ari Prasetyo; Alif Putra Pratama; Pramudya Ibnu Subrata (CITACONOMIA : Economic and Business Studies, 2026)
This conceptual research is driven by the fundamental shift in the global communication landscape from keyword-based Search Engine Optimization (SEO) toward generative AI-driven answer mechanisms. As public information consumption transitions to narrative synthesis produced by Large Language Models (LLMs), corporate entities face significant risks regarding informational authority and "AI Hallucinations," where models fabricate inaccurate factual output. This study aims to formulate a new conceptual framework, termed Hybrid GEO-PR, to safeguard corporate authenticity and maintain narrative integrity within this new digital ecosystem. Using an integrative literature review method and a case study framework focused on GoTo Group, the research synthesizes diverse theoretical perspectives to bridge traditional strategic communication with rapid advancements in artificial intelligence. Findings indicate that Public Relations (PR) practitioners must transition from conventional media relations to curators of "machine-readable" data authority to ensure corporate narratives are accurately synthesized by autonomous assistants. The study identifies "radical transparency" and the synchronization of technical metadata with human narratives as essential defense mechanisms against algorithmic disinformation and market volatility. The research concludes that the effectiveness of modern public communication is no longer measured by media reach or static search rankings, but by the precision of AI-generated summaries and an organization's ability to serve as the "ground truth" for intelligent machines. This study provides a strategic roadmap for firms to maintain a coherent brand identity for both human audiences and AI systems.